Effect of compaction on physical properties of a sewage sludge and red gypsum mixture as intermediate landfill cover - Rosli N.A.; Aziz H.A.; Selamat M.R.; Lim L.L.P.; Zawawi M.H. (Elsevier Ltd, 2023)
Chemical oxygen demand; Compaction; Compressive strength; Granular materials; Gypsum; Leachate treatment; Mixtures; Sewage sludge; Column test; Compaction degree; Constant head; Degree conditions; Degree of compaction; Landfill covers; Property; Red gypsum; Unconfined compressive strength; Wastes recycling; Hydraulic conductivity